Stage I-IV Colorectal Cancer Prognosis Can Be Predicted by Type and Number of Intratumoral Macrophages and CLEVER-1(+) Vessel Density - Ålgars Annika; Kemppinen Lotta; Fair-Mäkelä Ruth; Mustonen Harri; Haglund Caj; Jalkanen Sirpa (MDPI, 2022)
Simple Summary Tumor-associated macrophages can either promote or prevent cancer growth depending on factors such as macrophage polarization status, tumor type, and disease stage. Macrophages and vessels interact with each other, and the number of lymphatic vessels also affects cancer survival. CLEVER-1 is a protein expressed both on immunosuppressive M2 macrophages and lymphatic vessels. The aim of this study was to validate our previous results regarding the prognostic role of CLEVER-1(+) macrophages, CD68(+) macrophages, and CLEVER-1(+) lymphatic vessels in stage I-IV colorectal cancer. The results indicate that the prognostic role of tumor-associated macrophages and lymphatic vessels changes during disease progression. The findings resemble our earlier results, but are not completely equal, which may be due to the different types of tumor samples used in the two studies (whole section vs. tissue microarray). Macrophages, which are key players in the tumor microenvironment and affect the prognosis of many cancers, interact with lymphatic vessels in tumor tissue. However, the prognostic role of tumor-associated macrophages (TAM) and lymphatic vessels in human colorectal cancer (CRC) remains controversial. We investigated the prognostic role of CD68(+) and CLEVER-1(+) (common lymphatic endothelial and vascular endothelial receptor 1) TAMs in addition to CLEVER-1(+) lymphatic vessels in 498 stage I-IV CRC patients. The molecular markers were detected by immunohistochemical (IHC) analysis. The results showed that, in early stage I CRC and in young patients (age below median, <= 67.4 years), a high number of CD68(+) and CLEVER-1(+) TAMs was associated with longer disease-specific survival (DSS). In early stage I CRC, high intratumoral CLEVER-1(+) lymphatic vessel density (LVD) predicted a favorable prognosis, whereas the opposite pattern was observed in stage II CRC. The highest density of CLEVER-1(+) lymphatic vessels was found in metastatic disease. The combination of intratumoral CLEVER-1(+) lymphatic vessel(high) + CD68(+) TAM(low) was associated with poor DSS in stage I-IV rectal cancer. The present results indicate that the prognostic significance of intratumoral macrophages and CLEVER-1(+) lymphatic vessels differs according to disease stage, reflecting the dynamic changes occurring in the tumor microenvironment during disease progression.